Folding as a precursor of asymmetric boudinage in shear zones affecting migmatitic terranes - Pamplona, J. (2014)
The folding laws control the process responsible for the genesis and the initial morphological evolution of shearband boudins. In this model, the generation of boudins begins with folding of tabular competent veins of different thickness immersed in a less competent matrix. Veins thicker than a given critical value form initial asymmetric open folds that evolve by asymmetric antithetical rotation and later by an internal mass redistribution with translation along the interface vein-matrix. On the other side, the veins thinner than the critical value follow the folding process until it culminates with the coalescence and stacking of the folds. By this mechanism the critical thickness is reached and these bodies are prone to suffer a new phase of boudinage similar to that followed by the originally thicker veins. Therefore, all deformed tabular veins, embedded in a ductile matrix, converge to classical shearband boudin morphology, independently from their original thickness.